Fire training of students specialty «Law Enforcement Activity» with the use of elements of combat horting methods - Melnyk, Ivan; Kaniuka, Valerii; Bohaychuk, Volodymyr (Actual problems of law (Aktual’ni problemi pravoznavstva), 2022)
The issues of methods of forming students’ specialties “Law Enforcement Activity” skills and abilities to possess firearms are investigated in the article. It is justified that the study of the basics of shooting is closely related to the study of the material part of the weapon, techniques and rules of shooting. Emphasis is placed on the use of elements of combat horting techniques at different stages of fire training, as part of the training of future law enforcement officers. It is concluded that fire training should be built on the basis of knowledge and practical skills on the procedure and rules of use and application of firearms, safety measures when handling weapons, the material part of the weapon. If the future police officer will not know and master at least one of the topics of the course, it will appear his unprofessionalism and imperfect knowledge of fire training. Due to the increased danger of law enforcement officers, the threat to their lives and health, the police of foreign countries have long been conducting special training to ensure personal safety («security management»). The need to study a separate topic on security management with students has been identified. It is substantiated that the proposed and generalized recommendations on fire training of future law enforcement officers are not exhaustive. If there is a training program taking into account the individual characteristics of future law enforcement officers who are trained in fire training, these recommendations may be changed. At the same time, the law enforcement officer must be psychologically ready to use firearms against the offender, and he must be confident in the legitimacy of the use of firearms in such a situation.